Serum Progranulin Levels as Markers of Mammary Tumors in Women - Wahyuni, Rosa Dwi; Rahma, Rahma; Ngatimin, Dachruddin; M. Sabir, M. Sabir; Lewa, Abd. Farid (Poltekkes Kemenkes Palu, 2024)
Introduction: Carcinoma mammae is a malignant tumor that develops from breast cells and has the potential to invade the surrounding tissue (invasive) or metastasize to other parts of the body. While it is more frequently diagnosed in women, there are cases where it is also found in males. Purpose: This study aims to identify variations in serum progranulin levels as distinguishing factors between benign mammary tumors and mammary carcinoma. Method: The research adopts a quantitative approach with a cross-sectional design to ascertain the significance of serum progranulin levels in patients with mammary tumors. The study includes the entire accessible population diagnosed with mammary tumors by clinicians in the Surgical Oncology Department of Dr. Wahidin Sudirohusodo Teaching Hospital in Makassar, with a sample size of 78 individuals. Normality is assessed using the Kruskal-Wallis test, and differences are examined through the Mann-Whitney test. Result: A substantial difference exists in serum progranulin levels among breast carcinoma patients with benign mammary tumors and the control group (P<0.001). The mean difference in benign tumors is 121.08±56.84, whereas in breast carcinoma, it is 239.54±34.79. Conclusion: Serum progranulin levels can be employed as a potential alternative for diagnostic support in the early detection of both benign mammary tumors and mammary carcinoma.